2006
DOI: 10.1152/ajpgi.00543.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin receptors in rat and human nodose ganglia: putative role in regulating CB-1 and MCH receptor abundance

Abstract: Intact vagal afferent neurons are required for the satiety effects of the intestinal hormone cholecystokinin (CCK) and the orexigenic effects of the gastric regulatory peptide ghrelin. In this study, we examined the localization of ghrelin receptors in nodose ganglia and their function in regulating the expression of other orexigenic receptors, notably cannabinoid (CB)-1 and melanin-concentrating hormone (MCH)-1 receptors. With the use of RT-PCR, transcripts corresponding to both functional [growth hormone sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
2
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 35 publications
(61 reference statements)
5
160
2
2
Order By: Relevance
“…38 Importantly, ghrelin reverses the negative control on CB 1 expression by CCK in the nodose ganglion. 39 These data indicate that, as seen in the hypothalamus and NAcS, EC tone changes in the brainstem during the different phases of eating, the highest being after food deprivation and the lowest during food consumption, an effect that is possibly because of the opposing regulatory effects of CCK and ghrelin.…”
Section: Brief Introduction To the Endocannabinoid Systemmentioning
confidence: 79%
“…38 Importantly, ghrelin reverses the negative control on CB 1 expression by CCK in the nodose ganglion. 39 These data indicate that, as seen in the hypothalamus and NAcS, EC tone changes in the brainstem during the different phases of eating, the highest being after food deprivation and the lowest during food consumption, an effect that is possibly because of the opposing regulatory effects of CCK and ghrelin.…”
Section: Brief Introduction To the Endocannabinoid Systemmentioning
confidence: 79%
“…Ghrelin's appetite-stimulating effect was abolished in rats with subdiaphragmatic vagotomy and in rats with capsaicin-induced vagal deafferentation (Date et al, 2002). Ghrelin receptor is expressed by a subset of vagal afferent neurons in the nodose ganglia and appears to regulate expression of other peptide receptors in vagal afferents (Date et al, 2002;Burdyga et al, 2006). Furthermore, ghrelin does not stimulate food intake in patients with surgical procedures involving vagotomy (le Roux et al, 2005).…”
Section: Stomach: Stretch Tension Leptin and Ghrelinmentioning
confidence: 99%
“…GHS-Rs are widely distributed in the brain and GHS-R mRNA has been localized to the nodose ganglion, the site of vagal afferent cell bodies. 6 Ghrelin-producing neurons have also been identified in the brain, including hypothalamic sites. Recent work has clearly shown that vagal afferent fibers are not necessary for the stimulation of food intake.…”
Section: Meal Initiationmentioning
confidence: 99%